Coil therapy for patients with severe emphysema and bilateral incomplete fissures - effectiveness and complications after 1-year follow-up: a single-center experience - Kontogianni, Konstantina; Gompelmann, Daniela; Schuhmann, Maren; Hoffmann, Hans; Heußel, Claus Peter; Herth, Felix; Eberhardt, Ralf (The International journal of chronic obstructive pulmonary disease, 2017)
Coil therapy for patients with severe emphysema and bilateral incomplete fissures – effectiveness and complications after 1-year follow-up: a single-center experience Konstantina Kontogianni,1,2 Vasiliki Gerovasili,3 Daniela Gompelmann,1,2 Maren Schuhmann,1,2 Hans Hoffmann,2,4 Claus Peter Heussel,2,5 Felix JF Herth,1,2 Ralf Eberhardt1,2 1Department of Pulmonology and Respiratory Care Medicine, Thoraxklinik at the University of Heidelberg, 2Translational Lung Research Center Heidelberg, Member of the German Center for Lung Research DZL, Heidelberg, Germany; 3Department of Respiratory Medicine, Harefield Hospital, Royal Brompton & Harefield NHS Foundation Trust, London, UK; 4Department of Thoracic Surgery, Thoraxklinik at the University of Heidelberg, 5Diagnostic and Interventional Radiology with Nuclear Medicine, Thoraxklinik at the University of Heidelberg, Heidelberg, Germany Background: Lung volume reduction coil (LVRC) treatment is established in daily endoscopic lung volume reduction routine. The aim of this study was to evaluate the safety and efficacy of LVRC treatment.Patients and methods: This was a retrospective analysis of 86 patients (male/female: 40/46, mean age: 64±7 years) with severe COPD and bilateral incomplete fissures. A total of 10 coils were unilaterally implanted in a single lobe, and 28 out of 86 patients were treated bilaterally. At 90-, 180-, and 365-day follow-up, changes in pulmonary function test (PFT), 6-minute walk test (6MWT) and modified Medical Research Council (mMRC) dyspnea scale, as well as possible complications, were recorded.Results: At 90 days, the forced expiratory volume in 1 second did improve (P<0.001), but the improvement was not sustained at the 180- and 365-day follow-up (baseline: 0.71±0.21 vs 0.77±0.23 vs 0.73±0.22 vs 0.70±0.18 L). Both vital capacity and residual volume improved significantly (P<0.001) at the 90- and 180-day follow-up, but the improvement was lost after 365 days. Total lung capacity decreased at the 90-day follow-up but returned to baseline values at the 180- and 365-day follow-up. 6MWT (P=0.01) and mMRC (P=0.007) also improved at 90 and 180 days (Δ6MWT of 31±54 and 20±60 m, respectively), but the improvement was also lost at the 365-day follow-up. No significant further improvement was evident at any point in the follow-up after the second procedure. A total of 4 out of 86 patients passed away due to complications. Significant complications in the first 3 months and then at 12 months included the following: severe hemoptysis in 4 (3.5%) and 4 (3.5%) patients, pneumonia requiring hospitalization in 32 (28.1%) and 9 (7.9%) patients and pneumothorax in 7 (6.1%) and 2 (1.7%) patients, respectively. Milder adverse events included self-limited hemoptysis, pneumonias, or COPD exacerbations treated orally.Conclusion: LVRC improved PFT, 6MWT and mMRC initially, but the improvement was lost after 365 days. Furthermore, we observed 4 deaths and significant severe complications, which need to be further elucidated.Keywords: COPD, emphysema, bronchoscopy, coils, effectiveness, complications
Published 23 January 2017
Gesehen am 13.11.2018